2016
DOI: 10.1186/s40711-016-0044-z
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic statuses across generations and coresidence in China

Abstract: The aim of this study is to investigate the influences of the socioeconomic status of both older parents and their children on coresidential living arrangements, hence the microlevel mechanism of the formation of coresidence, in order to trace the patterns of family change in China. Starting with the assumption that the extended family system is no longer a binding cultural ideal in China, this study formulates a new explanation that living arrangements between older parents and their adult children are influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…In the Netherlands, Smits et al (2010) found that both adult children's and parents’ incomes were negatively associated with IC. Similar results have been reported in other contexts such as China (Chen & Chen, 2016) and Chile (Palma, 2021). As previously mentioned, research has also shown an association between intergenerational households and the response to crisis or economic difficulties, especially among younger individuals.…”
Section: Intergenerational Coresidence Across Sociodemographic Groupssupporting
confidence: 89%
“…In the Netherlands, Smits et al (2010) found that both adult children's and parents’ incomes were negatively associated with IC. Similar results have been reported in other contexts such as China (Chen & Chen, 2016) and Chile (Palma, 2021). As previously mentioned, research has also shown an association between intergenerational households and the response to crisis or economic difficulties, especially among younger individuals.…”
Section: Intergenerational Coresidence Across Sociodemographic Groupssupporting
confidence: 89%
“…The progress of modernization has brought about changes in individual cognition, family demographics, etc., thus leading to the looseness of the traditional family structure. Intergenerational living reflects the organization of family life and the way family members interact ( 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…The scale included ten subitems. The 4-point responses were rescaled from little or no (0) to most of the time ( 3 ). The total score was between 0 and 30.…”
Section: Methodsmentioning
confidence: 99%
“…Approximately 50% of middle-aged and elderly couples care for their grandchildren as families or individuals ( 1 ). With increasing life expectancy, more Chinese older adults can take care of their grandchildren ( 2 ), sharing time pressure and living costs with adult children's families ( 3 ). Chinese grandparents play an increasingly important role in caring for their grandchildren.…”
Section: Introductionmentioning
confidence: 99%